Hegel's philosophical psychology - Herrmann-Sinai, Susanne; Ziglioli, Lucia (Routledge, 2016)
pt. 1. Philosophy of subjective spirit -- pt. 2. Theoretical spirit -- pt. 3. Practical and free spirit -- pt. 4. The challenge of Hegel's philosophical psychology.
Elektronische Reproduktion der Druckausgabe
Keywords: Hegel, Georg Wilhelm Friedrich -- 1770-1831; Aufsatzsammlung; Philosophische Psychologie; Hegel, Georg Wilhelm Friedrich; Subjektiver Geist